MERPL: A more memory-efficient storing mode in RPL - Wei Gan; Zhiqiang Shi; Chen Zhang; Limin Sun; Ionescu, Dan (Proceedings - IEEE International Conference on Networks, 2013)
The IPv6 Routing Protocol for Low-power and Lossy Networks (RPL) allows a node to operate in storing or non-storing mode. However, as the network size increases, non-storing RPL will introduce lots of communication overhead, while storing RPL will consume lots of memory. In this paper, we improve the storing mode in RPL by reducing the memory consumption. Our performance studies show that our scheme effectively reduces communication overhead compared with the pure non-storing mode. In addition, it makes sure that the number of routing table entry stored in a node does not exceed a pre-specified factor N. When a node stores N routing table entries, it still has enough memory to run the node program and store the collected sensor data. Even when the size of network is large, nodes near the root can still provide adequate space to store the routing table entries using our scheme, but in pure storing mode they may not.